PENGARUH FAKTOR LINGKUNGAN TERHADAP JUMLAH BAKTERI UDARA KAMAR MANDI - Sriwulan Sriwulan; Rizqi Tri Bachtiar; Dian Asrofi; Diah Ayu Safitri; Nia Nurfitria; Kuntum Febriyantiningrum (Prodi Biologi Universitas PGRI Ronggolawe, 2023)
The bathroom is a damp area that has a variety of microorganisms. It is feared that these microorganisms can cause health problems. This study aims to determine the effect of environmental factors, in this case temperature, humidity, and light intensity on the number of air bacteria in the bathroom. Sampling of bathroom air bacteria in the UNIROW environment was randomly selected as many as 4 bathrooms, then the number of air bacteria was counted using the TPC (Total Plate Count) method at the UNIROW Biology Laboratory. Measurement of environmental factors in the form of light intensity, temperature, and humidity of the bathroom. The results of this study indicated that the highest air temperature at the 4 bathroom locations used as sampling locations was at KMKA, namely 300C with the lowest number of airborne bacteria, namely 83 colonies. While the lowest temperature was at KMMI (28.90C) with the highest number of airborne bacterial colonies (483 colonies). This shows that the higher the temperature, the lower the number of bacteria. The relative humidity in the four bathrooms ranges from 82% to 82.5%, but has a different number of airborne bacterial colonies. The higher the light intensity value, the lower the number of bacterial colonies counted. The results of the correlation analysis also showed that there was a significant correlation between light intensity and the number of bacterial colonies with a correlation coefficient of -0.99. Based on this, environmental factors have an influence on the number of bacteria in the bathroom